Design, Synthesis, and Evaluation of Camptothecin-Based Antibody–Drug Conjugates with High Hydrophilicity and Structural Stability - Xiong, Tingyu; Jin, Jiyu; Liu, Dongliang; Jin, Chen (Molecules (Basel, Switzerland), 2025)
In this study, we constructed a linear antibody–drug conjugate (ADC), 7300-LP1003, by coupling the camptothecin derivative 095 to a linker through an ether bond. In vitro enzyme experiments indicated that LP1003 releases 095 through the action of tissue cathepsin B. Therefore, we introduced lysine pairs with different water-soluble substituents to further modify the linker and synthesized side-chain ADCs 7300-LP3004 and 7300-LP2004, modified by polysarcosine and polyethylene glycol, respectively. In vitro experiments showed that, after incubation at 55 °C in phosphate-buffered saline for 48 h, 7300-LP3004 aggregation was 45.24%, which was significantly lower than that of 7300-LP1003 (77.14%). Cell cytotoxicity assays demonstrated that the side-chain ADCs, 7300-LP3004 and 7300-LP2004, exhibited significantly higher activity (IC50 values of 39.74 nM and 32.17 nM, respectively) compared to the linear ADC and 7300-Deruxtecan (IC50 of 186.5 nM and 124.5 nM, respectively). In the subcutaneous model of SHP-77 NOD scid gamma mice, when the ADC dose was 5 mg/kg, 7300-LP3004 showed the highest tumor inhibition rate with a tumor growth inhibition (TGI) of 106.09%, which was superior to that of the positive control 7300-Deruxtecan, which had a TGI of 103.95%. In conclusion, 7300-LP3004 demonstrated strong antitumor activity and high physicochemical stability, highlighting the need for further research and development of ADC drugs.